STUDENT QUESTIONNAIRE OF PISA 2006 AND RASCH ANALYSIS - Fitriati (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2013)
PISA is one of the biggest international student assessments. The results of this study are frequently used to inform policy directions and to provide feedback to learning and teaching. However, due to country socioeconomic, cultural and language differences among the countries, the test instruments may not be funtioning in the same way in all culture. Those differences may cause non-equivalence of tests or or tests may not be fair among different cultures, which then challenges assumptions made about measurement equivalence. This study aims to examine the equivalence of motivation and self concept items on student questionnaires of PISA 2006 study whether fit Indonesia context or not. The study employed two analisis of Rasch model to seek the equivalence of the tests. The results revealed that there is no significant DIF on motivation scale. One important finding of DIF analysis using Indonesia data was that two items of self-concept scale have been shown favoring males. The study also found that all items on motivation and self concept scale fit the data set and are not dependent on upon the sample of Indonesian students. The test is fair among different groups and contexts. This study suggests that more scales analysis is required as it will provide more comprehensive findings about the equivalence of this survey test.